If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 + -12a = 79 Solving 19 + -12a = 79 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + -12a = 79 + -19 Combine like terms: 19 + -19 = 0 0 + -12a = 79 + -19 -12a = 79 + -19 Combine like terms: 79 + -19 = 60 -12a = 60 Divide each side by '-12'. a = -5 Simplifying a = -5
| x^4-x^2-14x+54=0 | | 93.3=13b-10.7 | | 3x+5+4x=5 | | 4a-1=-37 | | g(0)=3x^2-2x | | 3+4x-18= | | 2-5x=3x-14 | | -5(x-4)=0 | | -216+125x^3=0 | | x+x+1+x+2=90 | | 5(r-5)=2(r-4)-4 | | 3a-19=-49 | | 2(x-3)=34 | | 4x-23=3x-5 | | 6x+9-5x=12 | | 42a^4+60a^3=0 | | 5z+7=6(z-2)-4(2z-3) | | -39=6+5t | | 25x+5(x+5)+10(x-9)=3,115 | | 3(x)=18 | | (5x^4)(25x^2)= | | x+(x+2)+(x+4)=-17 | | I-4I= | | 2x-5=-4x-2 | | 3x-1=x+21 | | -x+=7 | | 10s+19=119 | | 9x+14+2x=29 | | -9-2=9x+8-8x | | x+(x+1)+(x+2)+(x+3)=98 | | 7x+x-5x=25-2x | | 3x+4x=-8 |